MicroRNA Signature of Human Microvascular Endothelium Infected with Rickettsia rickettsii - Sahni, Abha (Int J Mol Sci, 2017)
MicroRNAs (miRNAs) mediate gene silencing by destabilization and/or translational repression of target mRNA. Infection of human microvascular endothelial cells as primary targets of Rickettsia rickettsii, the etiologic agent of Rocky Mountain spotted fever, triggers host responses appertaining to alterations in cellular gene expression. Microarray-based profiling of endothelial cells infected with R. rickettsii for 3 or 24 h revealed differential expression of 33 miRNAs, of which miRNAs129-5p, 200a-3p, 297, 200b-3p, and 595 were identified as the top five up-regulated miRNAs (5 to 20-fold, p ≤ 0.01) and miRNAs 301b-3p, 548a-3p, and 377-3p were down-regulated (2 to 3-fold, p ≤ 0.01). Changes in the expression of selected miRNAs were confirmed by q-RT-PCR in both in vitro and in vivo models of infection. As potential targets, expression of genes encoding NOTCH1, SMAD2, SMAD3, RIN2, SOD1, and SOD2 was either positively or negatively regulated. Using a miRNA-specific mimic or inhibitor, NOTCH1 was determined to be a target of miRNA 200a-3p in R. rickettsii-infected human dermal microvascular endothelial cells (HMECs). Predictive interactome mapping suggested the potential for miRNA-mediated modulation of regulatory gene networks underlying important host cell signaling pathways. This first demonstration of altered endothelial miRNA expression provides new insights into regulatory elements governing mechanisms of host responses and pathogenesis during human rickettsial infections.